1961
DOI: 10.1111/j.1476-5381.1961.tb01141.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Morphine on Some Sympathetically Innervated Effectors

Abstract: Morphine, in doses of 0.5 to 55 mg/kg, inhibited contraction of the nictitating membrane of the cat following stimulation of the postganglionic sympathetic nerve fibres. Morphine was more effective at low than at high frequencies of stimulation, independently of the size of contraction of the membrane; the speed of contraction was reduced at all frequencies. Cocaine potentiated the contraction of the nictitating membrane following nerve stimulation more at low than at high frequencies, and antagonized the acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1

Year Published

1964
1964
1982
1982

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 12 publications
1
28
1
Order By: Relevance
“…Morphine does not reduce the noradrenaline output from the vas deferens (Henderson & Hughes, 1976) or the cat nictitating membrane (Cairnie, Kosterlitz & Taylor, 1961) during trains of high-frequency impulses, This is consistent with the effects of morphine on the ej.p. By the time a steady-state e.j.p.…”
Section: Resultssupporting
confidence: 73%
“…Morphine does not reduce the noradrenaline output from the vas deferens (Henderson & Hughes, 1976) or the cat nictitating membrane (Cairnie, Kosterlitz & Taylor, 1961) during trains of high-frequency impulses, This is consistent with the effects of morphine on the ej.p. By the time a steady-state e.j.p.…”
Section: Resultssupporting
confidence: 73%
“…In six experiments we found no evidence which suggested that morphine, in doses large enough to depress the responses of the nictitating membrane (Cairnie et al, 1961), interfered with impulse transmission. In the example shown in Fig.…”
Section: Resultsmentioning
confidence: 62%
“…It has been shown (Kosterlitz & Taylor, 1959;Cairnie et al, 1961) that the depressant action of morphine on the responses of the rabbit sinoatrial node to vagal stimulation and on the response of the cat nictitating membrane to postganglionic sympathetic stimulation is greater at low than at high stimulus frequen-cies. We were therefore particularly interested in the possible action of morphine on action potentials evoked by single stimuli, but included also experiments with repetitive stimulation.…”
mentioning
confidence: 99%
“…Just as tolerance is not shown clinically to all the central actions of morphine, in the present paper there is one action which is not suppressed, namely the potentiating action of adrenaline on the tibialis anterior response to direct muscle stimulation (Huidobro, Cubillos & Eyzaguirre, 1952). Morphine has already been shown to have a number of depressant actions: for example, on cerebral metabolism (Takemori, 1962;Clouet, Ratner & Williams, 1966;Clouet & Ratner, 1968): on the responses of the nictitating membrane to pre-or postganglionic stimulation (Trendelenburg, 1957;Cairnie, Kosterlitz & Taylor, 1961;Gyang, Kosterlitz & Lees, 1964); on the cardiac responses to vagal stimulation (Kosterlitz & Taylor, 1959;Kennedy & West, 1967) and on the release of the chemical transmitter, acetylcholine (Paton, 1957;Schaumann, 1957). Morphine can suppress the actions of a number of drugs at the peripheral receptors (Trendelenburg, 1957;Kosterlitz & Robinson, 1958 Cairnie et al (1961) found that morphine did not decrease the nictitating membrane contraction induced by adrenaline or noradrenaline.…”
Section: Discussionmentioning
confidence: 99%